Perfusion index and lactate clearance as microcirculation parameters in pediatric post-cardiac correction surgery - Prawira, Yogi; Silawati, Trisna; Kaswandani2, Nastiti (Paediatrica Indonesiana, 2025)
Background Congenital heart disease (CHD) is a common congenital anomaly in children, with corrective cardiac surgery using cardiopulmonary bypass (CPB) being the definitive treatment. However, post-operative morbidity and mortality remain high, requiring effective hemodynamic monitoring in the cardiac intensive care unit (CICU). Blood lactate levels are traditionally used to assess microcirculation, while non-invasive methods like the perfusion index (PI) have gained interest for real-time monitoring. Objective To determine the correlation between PI and blood lactate levels in pediatric patients following corrective cardiac surgery. Methods A prospective cohort study was conducted in the cardiac intensive care unit (CICU) at Cipto Mangunkusumo Hospital from September to October 2024. Thirty-four pediatric patients aged 1 month to 18 years who underwent corrective cardiac surgery were included. PI and lactate levels were measured at one, four, and eight hours post-operation. Results The median age of participants was 21.5 (IQR 10.25–79.5) months. Non-cyanotic CHD was the most common diagnosis (58%), and 67.6% of cases involved CPB. Low cardiac output syndrome occurred in 17.6% of subjects. Lactate levels decreased significantly over time (P<0.001), while PI showed an increasing trend. Correlation analysis revealed a significant negative correlation between PI <1.4 and lactate levels at the fourth (r =-0.455; P=0.038) and eighth hours (r=-0.515; P=0.017). Conclusion  PI has a significant negative correlation with lactate levels and may serve as a useful non-invasive parameter for microcirculation monitoring in pediatric patients after corrective cardiac surgery.